Potret Kenakalan Remaja dalam Novel Dignitate karya Hana Margaretha - Tegar, M.; Adek, Muhammad (Universitas Negeri Padang, 2024)
This research aims to explain the different forms of juvenile delinquency, the factors that contribute to it, and the impact it has in the novel Dignitate by Hana Margaretha. The theory used in this study is literary sociology theory. The research employs a descriptive method and utilizes the novel Dignitate by Hana Margaretha as the primary source of data. The study results show that there are two forms of juvenile delinquency: (1) delinquency that does not violate the law and (2) delinquency that does violate the law. Additionally, the factors contributing to juvenile delinquency can be categorized into two types: internal factors, which originate from the teenagers themselves, and external factors, which come from outside influences like the family environment and the community environment. Lastly, the impact of juvenile delinquency manifests in three ways: affecting the teenagers themselves, impacting the family, and influencing society as a whole.